Financial Performance Of Kendari Health Polytechnic Before And During The Covid-19 Pandemic - Rochmad Munandar; Cepi Pahlevi; Fauzi R. Rahim (International Journal of Business and Quality Research, 2023)
This study aims to determine whether there is a difference in the Financial Performance of the Kendari Health Polytechnic before and during the Covid-19 pandemic in the period before the Covid-19 pandemic began in 2017, 2018 and 2019. Meanwhile, the period when the Covid-19 pandemic occurred began in 2020, 2021 and 2022. The data used are the financial statements of the Kendari Health Polytechnic in the form of Budget Realization Reports, Balance Sheets, Operational Reports and Reports on Changes in Equity for 2017, 2018, 2019, 2020, 2021 and 2022. The data was analyzed by the cumulative method with the Financial Performance Ratio analysis tool referring to Per 32/PB/2014. Financial performance measured is Current Ratio, Fixed Asset Turnover, Return on Fixed Assets, Return on Equity, PNBP Income to Operating Expenses (POBO). The financial performance ratio is used as a variable and the Normality Test is then analyzed using the Paired Sample T Test. The results of the statistical test show that all five groups of financial ratios tested have Asymp values. Sig. (2-tailed) is greater than 0.05 so it can be concluded that there is no significant difference in the Financial Performance of Kendari Health Polytechnic before and during the Covid-19 pandemic. Key words: Financial performance, Before and during Covid-19 Pandemic